What is your earliest memory? It depends. Issue 6 (3rd July 2021) - Peterson, Carole
ABSTRACT: This article is a selective review of the literature on childhood amnesia, followed by new analyses of both published and unpublished data that has been collected in my laboratory over two decades. Analyses point to the fluidity of people's earliest memories; furthermore, methodological variation leads to individuals recalling memories from substantially earlier in their lives. How early one's "earliest" memory is depends on whether you have multiple interviews, how many early memories were requested within an interview, the type of interview, participation in prior tasks, etc. As well, people often provide chronologically earlier memories within the same interview in which they later identify a chronologically older memory as their "earliest". There may also be systematic mis-dating to older ages of very early memories. Overall, people may have a lot more memories from their preschool years than is widely believed, and be able to recall events from earlier in their lives than has been historically documented.